1996
DOI: 10.1001/archinte.1996.00440060103013
|View full text |Cite
|
Sign up to set email alerts
|

Erythromycin-Induced Clozapine Toxic Reaction

Abstract: Clozapine, used in the treatment of patients with schizophrenia resistant to other neuroleptic medication, is metabolized by the hepatic microsomal system to demethyl-clozapine and clozapine-N-oxide. Changes in clozapine serum concentrations have been documented after initiation of therapy with medications known to induce or inhibit liver microsomal enzymes. These interactions are of clinical importance when diminished efficacy or increased toxic effects of clozapine therapy occur. A 34-year-old schizophrenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Although it appears that CYP3A4 is without common functional polymorphisms (Hiratsuka, 2012), it has been shown that nonsynonymous alleles for CYP3A4 encode enzymes with altered catalytic properties (Dai et al, 2001;Eiselt et al, 2001;Zhang et al, 2008). Inducers that increase the activity of CYP3A4 (Cohen et al, 1996;Jerling et al, 1994) could be more important than genetic polymorphism of this enzyme for the individual variability in CLZ bioactivation. Although CYP2D6 showed relatively high specific activity in all three oxidative pathways of CLZ-metabolism (Table 1), the CYP2D6-specific inhibitor quinidine showed no or only minor inhibition of these pathways in incubations of CLZ with the 100 individual HLM fractions (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although it appears that CYP3A4 is without common functional polymorphisms (Hiratsuka, 2012), it has been shown that nonsynonymous alleles for CYP3A4 encode enzymes with altered catalytic properties (Dai et al, 2001;Eiselt et al, 2001;Zhang et al, 2008). Inducers that increase the activity of CYP3A4 (Cohen et al, 1996;Jerling et al, 1994) could be more important than genetic polymorphism of this enzyme for the individual variability in CLZ bioactivation. Although CYP2D6 showed relatively high specific activity in all three oxidative pathways of CLZ-metabolism (Table 1), the CYP2D6-specific inhibitor quinidine showed no or only minor inhibition of these pathways in incubations of CLZ with the 100 individual HLM fractions (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the established role of CYP1A2, there have also been a number of clinical reports that have implicated CYP3A4 in CLZ elimination. Thus, erythromycin increased CLZ plasma levels and precipitated seizures or other adverse drug interactions in some patients (Funderburg et al, 1994;Cohen et al, 1996;Edge et al, 1997). Likewise, coadministration of the selective serotonin reuptake inhibitor drugs fluoxetine and paroxetine increased serum concentrations of CLZ up to 60% over control in some patients, possibly due to inhibition of CYP3A4 (Centorrino et al, 1994(Centorrino et al, , 1996Wetzel et al, 1998;Diaz et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Controversial findings have been reported concerning the interaction between erythromycin, a macrolide antibiotic with a strong inhibitory effect on CYP3A4, and clozapine. Case reports have indicated that concomitant treatment with erythromycin resulted in an elevation of plasma clozapine levels, along with toxic effects [181,182]. Conversely, in a study in healthy subjects, no modifications in the disposition of clozapine during coadministration with erythromycin, suggesting a limited involvement of CYP3A4 in the metabolism of clozapine in humans [183].…”
Section: Clozapinementioning
confidence: 99%